Триплет-синглетний перехід при адсорбції молекули О2 на грані Si (111) - Terebinskaya, M. I.; Filonenko, O. V.; Tkachuk, O. I.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2015)
Calculations of optimal spatial structure (TFG, B3LYP, 6-31G **) adsorption complex molecules of oxygen on the cluster medeliruyuschem face of the Si (111), showed that at distances greater than 0.35 nm, the axis perpendicular to the surface of the molecule and a molecule of O2 is in the triplet state. At lower values of this distance occurs singlet-triplet transition, which provides binding molecules of O2 silicon surface. Using the calculated data performed otsenkaveroyatnosti triplet-singlet transitions in the adsorption complex.